ChemInform Abstract: The Stannides Ln2Ni2Sn (Ln: Pr, Ho, Er, Tm) — Structural Transition from the W2B2Co to the Mo2B2Fe Type as a Function of the Rare Earth Size. Issue 16 (28th March 2013) - Heying, Birgit; Rodewald, Ute Ch.; Chevalier, Bernard; Poettgen, Rainer
Abstract The title compounds are synthesized by arc‐melting of the elements followed by annealing at 1070 K for one week.